Strengthening Civic Character Through The Integration Of Equality And Local Culture - Dyta Agnes Layung Sari; Marzuki, Marzuki; Khoirotul Bariyah; Eny Wahyu Suryanti (International Journal of Technology and Education Research, 2025)
Character degradation affects the personality of the nation and has the potential for regression. Therefore, strengthening the character of citizenship is an important study with an integration strategy in various activities (samaptaan, local culture) at SMAN 1 Giri Banyuwangi. The use of various activities in schools to strengthen civic character is the right step for the next generation to be globally intelligent and have a national character. Using a qualitative approach of case studies, this study produced the following findings: (1) activities of equality and local culture, strengthening civic character based on the PPK program, as a harmonization of ethics, aesthetics, and kinesthetics; school culture and extracurricular approaches to form civic virtue of the nation's successors in accordance with the national pillars (Pancasila, 1945 Constitution, NKRI, Bhinneka Tunggal Ika); (2) supporters: the care of the Police, the Indonesian Army/Navy, the Battalion organization; mandatory enforcement; funding from schools, students, business funds, sponsors; Health Protocols